Evaluation of energetic metabolism of horses in long-distance exercise: Accutrend® Plus versus laboratory - Duarte, P. C.; Souza, R. F.; Almeida, R. M.; Balsamão, G. M.; Ferraz, G. C. [UNESP]; Teixeira Neto, A. R. (Springer Nature, 2015)
The use of human equipment in veterinary medicine is very common; therefore, it is essential that it is tested and validated. In this study, a comparison was made between blood levels of glucose, lactate, triglycerides, and cholesterol obtained by the portable device Accutrend® Plus and those found in laboratory methods considered standard for the measurement of parameters of 11 Arabian (and Arabian crossed) horses which completed prolonged endurance effort. Collection was made in five stages: during rest, after 66 km, at the end of the race of 160 km, and 2 and 15 h after the race. Three venous blood samples were collected, the first being used immediately for the measurement of the parameters on the portable device and the other two—with sodium fluoride and without anticoagulant—were packed and immediately sent to a reference laboratory. Statistical analysis consisted of the Student’s t test, Pearson correlation, and graphic representation of Bland and Altman (1986) to compare the two measurement methods and Tukey’s test for evaluating the effect of variation in relation to the effort according to the standard laboratory method for parameter measurement. Agreement and correlation were not found between the values of glucose, lactate, triglycerides, and blood cholesterol measured by the portable device Accutrend® Plus and the referenced laboratory methods for these parameters in horses undergoing the endurance test, which reinforces the need for more research to definitely validate or invalidate the use of this technology for the species.
Keywords: Biochemistry; Endurance; Horse; Portable